When ransomware strikes, what's your recovery plan?. Issue 7 (July 2021) - Young, Stephen
Abstract : Preventing a ransomware attack requires a tiered approach utilising a defence-in-depth methodology. This incorporates user training, email filtering, virus detection, firewall configuration, edge security and activity monitoring, combined with an array of additional techniques where budget, resources and expertise allow.